Surfactant-Controlled Synthesis of Mesoporous Silica from Oil Palm Empty Fruit Bunch - Tri Partuti; Donanta Dhaneswara; Jaka Fajar Fatriansyah; Muflikhah Muflikhah; Maria Christina Prihatiningsih (EduChemia: Jurnal Kimia dan Pendidikan, 2026)
Indonesia is the country that produces the most palm oil worldwide, generating large amounts of oil palm empty fruit bunch (EFB) waste containing silica. The use of EFB waste as a silica precursor offers a sustainable alternative to conventional synthetic sources. Therefore, this study aims to synthesize mesoporous silica from EFB ash via a sol-gel method, using single and mixed surfactant systems, namely, cetyltrimethylammonium bromide (CTAB), Pluronic P123 (P123), and a mixture of CTAB-P123, with a constant mass of 5 grams. The properties of mesoporous silica derived from EFB were characterized using X-ray fluorescence (XRF), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy equipped with energy-dispersive X-ray analysis (SEM-EDX), transmission electron microscopy (TEM), small-angle X-ray scattering (SAXS), and nitrogen adsorption‒desorption measurements based on the BET and BJH methods. The results of this study revealed that the use of Pluronic P123 resulted in a specific surface area of 317.085 m²/g, CTAB (519.951 m²/g), and a mixed-surfactant system (496.547 m2/g). The SAXS results revealed that a mixed CTAB-P123 system produced an ordered mesostructure with a distinct peak at q = 0.1005 Å-1, while a single surfactant formed disordered mesopores. These results demonstrate that the type of surfactant performs an essential function in tailoring the mesoporous characteristics of EFB-derived silica.